Fitness- and appearance-related self-conscious emotions and sport experiences: A prospective longitudinal investigation among adolescent girls. (March 2020) - Pila, Eva; Sabiston, Catherine M.; Mack, Diane E.; Wilson, Philip M.; Brunet, Jennifer; Kowalski, Kent C.; Crocker, Peter R.E.
Abstract: Despite well-documented benefits of sport participation for adolescents, girls are less likely to initiate participation and more likely to disengage from sport, compared to boys. Due to the highly evaluative and social nature of the sport context, girls' emotional experiences around their body's abilities, function, and fitness are important – yet understudied – predictors of sport participation. The objectives of this longitudinal study were to describe changes in fitness-related and appearance-related self-conscious emotions (i.e., guilt, shame, authentic pride, hubristic pride) and sport experiences (i.e., sport commitment, enjoyment, anxiety) over time, and examine whether between- and within-person differences in these emotions predict sport experiences during adolescence. A sample of 518 girls involved in organized sport completed questionnaires once a year over a three-year period. Results from multilevel models reveal detrimental changes in emotions, sport commitment and enjoyment over time. Further, fitness-related emotions remain significant predictors of sport experiences above and beyond appearance-related emotions thus highlighting the importance of fitness-related emotions in predicting sport experiences. Examining both between and within-person effects is novel in elucidating the predictive capacity of fitness-related emotions as they explain differences between girls – as well as variations in girls' sport experiences over time. Highlights: Fitness-related shame and guilt increased; pride, sport commitment and enjoyment decreased over 3-years. Girls with higher levels of fitness-related shame and guilt, and lower levels of pride reported worsened sport experiences. Girls reported poor sport experiences at times when all emotions were worse than their own average. Fitness-related self-conscious emotions contribute to sport experiences above and beyond appearance emotions.